Which health professionals are most at risk for cardiovascular disease? Or do not be a manager - Sovova, Eliska; Nakladalová, Marie; Kaletova, Marketa; Sovova, Marketa; Radova, Lenka; Kribska, Michaela (International journal of occupational medicine and environmental health, 2014)
OBJECTIVES: Health care workers constitute a high-risk occupational category owing to the character of their work that includes high-risk environment, shift work and mental as well as physical stress. In occupational medicine, caring for their health condition should be a priority and include measures aimed at preventing cardiovascular diseases. The study aimed at determining the prevalence of cardiovascular disease (CVD) risk factors in employees of a large hospital and assessing their effect on the incidence of cardiovascular events. MATERIALS AND METHODS: The group comprised 3124 employees with a mean age of 36.1 years (SD = 11.4), out of whom 562 were males (mean age of 37.1 years, range: 18-72; SD = 12.26) and 2562 were females (mean age of 35.9 years, range: 18-68; SD = 11.24). At their initial examination, the employees filled in a questionnaire on basic CVD risk factors (according to valid recommendations). This was supplemented with objective data to determine the risk of CVD using valid charts. From this group, a subset of persons at a high or intermediate risk was selected, comprising 247 individuals with a mean age of 54.1 years (SD = 5.73). After 5-9 years (mean 7.24±1.38 years), they either underwent another examination or their health status was ascertained by phone or in a computer database. The end point was the incidence of cardiovascular events (sudden death, acute myocardial infarction, unstable angina pectoris, percutaneous coronary intervention, cardiac failure, stroke or transient ischemic attack). RESULTS: The end point was noted in a total of 15 males (6.07%) and 6 females (2.42%), being statistically significantly present in managers (males p < 0.00007, females p < 0.00001), male physicians/surgeons (p < 0.025), tertiary-educated males (p < 0.0095), female smokers (p < 0.015), male ex-smokers (p < 0.007), overweight or obese males (p < 0.02) and those with the waist-to-hip ratio above 1.0 (p < 0.005). CONCLUSIONS: Cardiovascular events are most likely to occur in obese male physicians/surgeons holding managerial positions and in female managers.
Keywords: senioři; longitudinální studie; Obesity; Incidence; mladiství; sexuální faktory; nemoci z povolání; Middle Aged; mužské pohlaví; Physician Executives; incidence; Adult; mladý dospělý; personál nemocniční; Occupational Diseases; Cardiovascular Diseases; Young Adult; ženské pohlaví; Humans; Sex Factors; Personnel, Hospital; lidé středního věku; obezita; rizikové faktory; Longitudinal Studies; dospělí; Female; Aged; Risk Factors; Adolescent; ředitelé nemocnic; kardiovaskulární nemoci; lidé; Male